Competence-Oriented Independent Work of Students in Higher Education Institutions: Characteristics, Content and Organization - Ualiyeva, Nazym Toleubekovna; Murzalinova, Alma Zhakimovna; Kucher, Tatyana Pavlovna (International Review of Management and Marketing, 2016)
The purpose of this study involves characterization of competence-oriented independent work of students in the higher education institution and its effective organization within the framework of the competence-based training. According to the results of the study the characteristics and the content of independent work under study have been established, learning and teaching support materials have been presented. In accordance with the developed theoretical bases of the organization the competence-oriented independent work of students studying at the faculty "Pedagogy and methodology of primary education" has been defined and the influence of self-education and self-development skills on the development of students’ professional competence has been established. The personal importance of independent work as a sustainable motive for the future professional activity has been confirmed. The main conclusion is that the students’ independent work (SIW) is oriented to the creation of conditions for the gradual formation of the following groups of motives for independent educational-cognitive activity and educational research: self-realization, achievement, social belonging, and status. Keywords: competence-based approach to training, competence-oriented students’ independent work, learning and teaching support materials, training and professional task JEL Classifications: I20; I25; I26